Business ethics - Shaw, William H.
Prepare for your career with BUSINESS ETHICS with InfoTracđ! Filled with examples and introductions, this philosophy text introduces you to important philosophical concepts and principles via a range of perspectives such as social, historical, philosophical, and personal. Case studies include recent business scandals, Battling Over Bottled Water, An Internet Parasite, One Nation Under Wal-Mart, and Free Speech or False Advertising? Knowledge is reinforced through chapter summaries, illustrations, and suggested further readings